الالتزامات المنوطة بالصيادلة لضمان حماية المستهلك - لدغش, رحيمة (Revue jurisprudence, 2018)
تطبيقا لنصوص قانون الصحة، ولما ورد في كل من مدونة أخلاقيات مهنة الطب، والمراسيم التنفيذية المتعلقة بتسجيل المنتجات الصيدلانية المستعملة في الطب البشري وبرخصة استغلال المؤسسات لإنتاج المنتجات الصيدلانية وتوزيعها و بالإعلام الطبي والعلمي الخاص بالمنتجات الصيدلانية، فإنه يقع على عاتق الصيادلة عدة التزامات قصد حماية مستهلك المنتجات والمواد التي يقومون ببيعها، تتمثل هذه الالتزامات في : الالتزام بإعلام المستهلك بطريقة استعمال الدواء والنتائج والآثار التي قد تنشئ عن استعماله، و بضمان تقديم أدوية صالحة للاستعمال غير ضارة، والالتزام بالمطابقة وذلك بتقديم دواء مطابق لذلك المدون في الوصفة الطبية ، كما يتعين على الصيدلي أن ينفذ الوصفة الطبية بعد أن يراقب البيانات الرئيسية الواردة فيها، ويسلم دواء يتوافق مع حالة المريض، والتأكد من صلاحيته للغرض المستخدم فيه . هذه التزامات التي أكد عليه أيضا القانون رقم 09/03 ، المتعلق بحماية المستهلك وقمع الغش، ذلك أن مقتني المواد والمنتجات الصيدلانية، هو مستهلك باختلاف صفته في التعامل مع الصيدلي سواء كان مريض، أو مشترى عادي لهذه المواد . الكلمات المفتاحية : الصيدلي، المريض، المستهلك، المواد والمنتجات الصيدلانية، الوصفة الطبية، الالتزام بالإعلام، الضمان، مطابقة الدواء . Summary: Applying the provisions of the health Act and as stated in every code of ethics of the medical profession. and executive decrees concerning the registration of Pharmaceutical Products. used in human medicine, and a license to exploit institutions for the production and distribution of Pharmaceutical Products and medical media and the private Pharmaceutical Products and scientific, it is located on the shoulders of several Pharmacists in ordered to protect the consumer Products and multitude commitments they sell. These commitments are in: commitment of the consumer informs the way the use of medications and the results and effects that may create from using it. And ensuring the provision of medicines usable, not harmful. And sticking of conformity and providing medication is identical to that recorded in the medical prescription. The Pharmacist must be implemented prescription after watching the main data contained therein and delivers the medicine is compatible with the patient's condition and validated for the purpose for which the user. These commitment, which said also by the low n o 09/03 on consumer protection and the suppression of fraud that the collectors materials and Pharmaceutical Products is the consumer of altered described in dealing with the pharmacist. whether it is a patient or a regular buyer for this products.